Effects of winter convection on the deep layer of the Southern Adriatic Sea in 2012. Issue 11 (13th November 2013) - Bensi, M.; Cardin, V.; Rubino, A.; Notarstefano, G.; Poulain, P. M.
<x xml:space="preserve">Abstract</x> [1] We analyze aspects concerning the thermohaline changes observed in the near‐bottom layer of the Southern Adriatic Pit (SAP), in the Eastern Mediterranean, after the arrival of abundant and exceptionally dense water (σθ > 30 kg m−3) produced in the shallow Northern Adriatic Sea during winter 2012. For this purpose, we use temperature (T), salinity (S), and current time series collected at the E2M3A deep‐ocean observatory of the Southern Adriatic, and Conductivity‐Temperature‐Depth data obtained both in the Southern and Middle Adriatic from freely drifting profiling floats. The dense water produced in the Northern Adriatic arrived in the central and deepest part of the SAP as a series of individual pulses starting on 10 March 2012; while, a stronger and prolonged signal that significantly modified the local deep water stratification arrived after 10 April 2012. As a consequence, T and S suddenly decreased (≈0.15°C and ≈0.015), thus interrupting positive T and S bottom trends observed during the previous 5 years and producing a density increase of ≈0.02 kg m−3. Such variability has been rarely observed in the area. We ascribe its occurrence to the concomitance of exceptionally harsh and long‐lasting Bora wind, scarce precipitation, and low river discharge over the Northern Adriatic during winter 2011/2012. Eventually, this newly formed AdDW reached the Strait of Otranto during July 2012. Its characteristics profoundly differed from those observed in the previous decade. Hence, a noticeable variability in structure and circulation of the abyssal layers of the Ionian basin is likely to occur in the near future.